Advances in TENGs for Marine Energy Harvesting and In Situ Electrochemistry - Chuguo Zhang; Yijun Hao; Xiangqian Lu; Wei Su; Hongke Zhang; Zhong Lin Wang; Xiuhan Li (Nano-Micro Letters)
Highlights The basic information of triboelectric nanogenerator (TENG), the power conversion process, and key points of the marine energy harvesting TENGs was introduced in detail. An in-depth introduction and analysis of relevant research with the marine energy harvesting were conducted through gradient classification. This review not only provided a deeper summary of the latest research progress, discoveries, and challenges, but also made a rational outlook on solutions to related issues and future development directions.